2012
DOI: 10.1039/c2cp42535a
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous α-Fe2O3 thin films synthesized via the sol–gel process for light-driven water oxidation

Abstract: This work reports a facile and cost-effective method for synthesizing photoactive α-Fe(2)O(3) films as well as their performances when used as photoanodes for water oxidation. Transparent α-Fe(2)O(3) mesoporous films were fabricated by template-directed sol-gel chemistry coupled with the dip-coating approach, followed by annealing at various temperatures from 350 °C to 750 °C in air. α-Fe(2)O(3) films were characterized by X-ray diffraction, XPS, FE-SEM and electrochemical measurements. The photoelectrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 67 publications
3
52
0
2
Order By: Relevance
“…All films show wide absorption band edge upto 600 nm which is in agreement with result obtained by Hamd et al28 In optical absorption of compounds containing Fe 3+ cations have three types of electronic transitions are present i.e., Delivered by Publishing Technology to: University of North Carolina/ACQ Services IP: 170.164.50.90 On: Mon, 12 Oct 2015 02:SEM micrographs of Fe 2 O 3 thin films for various deposition temperatures. (i) ligand to metal charge-transfer transitions, (ii) Fe 3+ ligand field transition or the d-d transitions, and (iii) pair excitations resulting from the simultaneous excitations of two neighboring Fe 3+ cations that are magnetically coupled.…”
supporting
confidence: 91%
“…All films show wide absorption band edge upto 600 nm which is in agreement with result obtained by Hamd et al28 In optical absorption of compounds containing Fe 3+ cations have three types of electronic transitions are present i.e., Delivered by Publishing Technology to: University of North Carolina/ACQ Services IP: 170.164.50.90 On: Mon, 12 Oct 2015 02:SEM micrographs of Fe 2 O 3 thin films for various deposition temperatures. (i) ligand to metal charge-transfer transitions, (ii) Fe 3+ ligand field transition or the d-d transitions, and (iii) pair excitations resulting from the simultaneous excitations of two neighboring Fe 3+ cations that are magnetically coupled.…”
supporting
confidence: 91%
“…The best values are currently around 3 mA/cm 2 (at 1.23 V vs reference hydrogen electrode) 5, 10 for nanostructured films with an additional dopant to improve conductivity and a catalyst to reduce the overpotential. [4][5][11][12][13][14][15][16][17][18] Nanostructuration of the photoanode is used as a strategy to address the short diffusion length of holes in hematite by reducing the distance that photogenerated holes have to travel to reach the electrolyte. [4][5] 4 Nanostructuration of the hematite photoanode can be achieved by various methods, such as colloidal solution deposition [19][20][21][22] , electrochemical deposition [23][24][25][26] , spray pyrolysis 11, 27-28 , hydrothermal synthesis 13,[29][30] , atmospheric pressure chemical vapor deposition 5,31 or copolymerbased soft templating.…”
Section: Introductionmentioning
confidence: 99%
“…20 Zhang et al also observed that Fe 2 O 3 /TiO 2 heterostructures with high Fe contents (24 wt%) deposited by chemical vapor deposition on activated carbon bers allowed interesting photo-catalytic activities for the degradation of methyl orange. 36,37 Compared to other chemical approaches, 20,33 the sol-gel process allows a very good control of the lm microstructure through careful tuning of the sol composition, the heat treatment and the deposition conditions. [23][24][25] These results highlight the need for improving the morphology and the electronic structure of TiO 2 to tune separation and transportation of photo-excited charge carriers.…”
mentioning
confidence: 99%